(untitled) (International Conference on Education, Psychology and Humanities, 2026)
This article analyzes the problem of understanding Alisher Navoiy’s creative legacy based on the views put forward by the literary scholar Ozod Sharafiddinov in his article “Navoiy Lessons”. The study reveals manifestations of formality and superficiality in attitudes toward Navoiy’s heritage and substantiates the necessity of comprehending the poet’s works at the level of poetic essence. Within Sharafiddinov’s interpretation, the main components of Navoiy’s poetics - depth of artistic thinking, aesthetics of the word, and the artistic synthesis of philosophical and Sufi layers - are examined. The article emphasizes the need to study Navoiy’s oeuvre in connection with modern aesthetic thinking and evaluates Sharafiddinov’s views as an important methodological foundation for contemporary Navoiy studies.